Interplay of Physical and Social Vulnerabilities in Lumajang Coastal Areas: A Multidimensional Analysis with a Focus on Women's Education - Galisong, Ridwan Danuarta; Kholifah, Siti (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Coastal areas are a key element in maintaining global ecosystems and supporting economic and social activities. This research explores the role of women's education in reducing the vulnerability of the Lumajang coastal area through method analysis that includes field surveys, spatial analysis, and SWOT. The results of a spatial analysis combining physical and social data identify coastal areas as vulnerability zones. Furthermore, the SWOT analysis reveals opportunities for improving coastal women's education. The implication is that governments can allocate resources and implement more inclusive policies to improve women's education in the region, strengthening the resilience of coastal regions as a whole.